Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)= a-c+d-c+a-d
=2a-2c=2(a-c)
b)=-a-b+c-d+a-b-c-d
=-2b-2d
=2.(-b)-2d=2(-b-d)
c)=ab-ac-ad-ab-ac+ad
=-2.ac
1/(-37) +14+26+37
=[(-37)+37] +(14+26)
= 0 + 40
= 40
2/(-24) +6 +10+24
=[(-24)+24] +(10+6)
= 0 +16
=16
3/15+23+9+(-25) +9+(-23)
=[(-23)+23] +[(-25)+15] +(9+9)
= 0 + (-10) +18
= 0 + 8
= 8
4/60 +33 +(-50) +(-33)
=[(-33)+33]+[60 +(-50)]
= 0 + 10
= 10
5/(-16)+ (-209) + (-14) +209
=[(-209)+209] +[(-16)+(-14)]
= 0 +(-30)
= -30
6/(-12) +(-13)+36 +(-11)
=[(-12) +(-11)] +[ 36+(-13)]
= (-23) + 23
= 0
Chúc bn hok tốt !!!
1, (-37)+14+26+37=[(-37)+37]+14+26=0+40=40
2, (-24)+6+10+24=[(-24)+24]+6+10=0+16=16
3 , 15+23+(-25)+(-23)=[15+(-25)]+[23+(-23)]=-10
4, 60+33+(-50)+(-33)= [60+(-50)]+[33+(-33)]=10
5, (-16)+(-209)+(-14)+209=[(-16)+(-14)]+[(-209)+209]=-30
6, (-12)+(-13)+36+(-11)=[(-12)+(-11)]+[(-13)+36]=(-23)+23=0
Bài 1:
a; \(\dfrac{5}{18}\) + \(\dfrac{8}{19}\) - \(\dfrac{7}{21}\) + (- \(\dfrac{10}{36}\) + \(\dfrac{11}{19}\) + \(\dfrac{1}{3}\)) - \(\dfrac{5}{8}\)
= \(\dfrac{5}{18}\) + \(\dfrac{8}{19}\) - \(\dfrac{1}{3}\) -\(\dfrac{10}{36}\) + \(\dfrac{11}{19}\) + \(\dfrac{1}{3}\) - \(\dfrac{5}{8}\)
= (\(\dfrac{5}{18}\) - \(\dfrac{10}{36}\)) + (\(\dfrac{8}{19}\) + \(\dfrac{11}{19}\)) - (\(\dfrac{1}{3}\) - \(\dfrac{1}{3}\)) - \(\dfrac{5}{8}\)
= (\(\dfrac{5}{18}\) - \(\dfrac{5}{18}\)) + \(\dfrac{19}{19}\) - 0 - \(\dfrac{5}{8}\)
= 0 + 1 - \(\dfrac{5}{8}\)
= \(\dfrac{3}{8}\)
b; \(\dfrac{1}{13}\) + (\(\dfrac{-5}{18}\) - \(\dfrac{1}{13}\) + \(\dfrac{12}{17}\)) - (\(\dfrac{12}{17}\) - \(\dfrac{5}{18}\) + \(\dfrac{7}{5}\))
= \(\dfrac{1}{13}\) - \(\dfrac{5}{18}\) - \(\dfrac{1}{13}\) + \(\dfrac{12}{17}\) - \(\dfrac{12}{17}\) + \(\dfrac{5}{18}\) - \(\dfrac{7}{5}\)
= (\(\dfrac{1}{13}\) - \(\dfrac{1}{13}\)) + (\(\dfrac{12}{17}\) - \(\dfrac{12}{17}\)) + (-\(\dfrac{5}{18}\) + \(\dfrac{5}{18}\)) - \(\dfrac{7}{5}\)
= 0 + 0 + 0 - \(\dfrac{7}{5}\)
= - \(\dfrac{7}{5}\)
Bài 1 c;
\(\dfrac{15}{14}\) - (\(\dfrac{17}{23}\) - \(\dfrac{80}{87}\) + \(\dfrac{5}{4}\)) + (\(\dfrac{17}{23}\) - \(\dfrac{15}{14}\) + \(\dfrac{1}{4}\))
= \(\dfrac{15}{14}\) - \(\dfrac{17}{23}\) + \(\dfrac{80}{87}\) - \(\dfrac{5}{4}\) + \(\dfrac{17}{23}\) - \(\dfrac{15}{14}\) + \(\dfrac{1}{4}\)
= (\(\dfrac{15}{14}-\dfrac{15}{14}\)) + (\(-\dfrac{17}{23}+\dfrac{17}{23}\)) - (\(\dfrac{5}{4}\) - \(\dfrac{1}{4}\)) + \(\dfrac{80}{87}\)
= 0 + 0 - 1 + \(\dfrac{80}{87}\)
= - \(\dfrac{7}{87}\)
-57.11=-627
(+12).(+15)=180
(37-17).(5)+23.(-13-17)=-590
(-4).(+125).(-25).(-6).(-8)=60000
k nha
-57*11=627
12*25=300
(37-17)*5+23*(-13-17)=-665
(-5)*125*(-25)*(-6)*(-8)=750 000
Bài 1:
5; (-23) + 105
= 105 - 23
= 82
6; 78 + (-123)
= 78 - 123
= - (123 - 78)
= - 45
bài1
1)2763 + 152 = 2915
2)-7 +(-14)
=-(14 +7)
=-21
Bài 1 : bạn tự làm
Bài 2 :
1) (15+37)+(52-37-17) = 15 + 37 +52 - 37 - 17 = 50
2) (38 - 42 +14 ) - (25 - 27 -15 ) = 38 -42 +14 -25 +27 +15 = 27
3) - (21 - 32) - (-12 +32) = -21 +32 +12 -32 = -9
4) - (12 +21 -23) - (23 -21 +10) = -12 -21 +23 -23 +21 -10 = -22
5) (57-725) - (605 -53 ) = 57 -725 - 605 +53 = -1220
6) (55 +45 +15) - (15 -55 +45) = 55 +45 +15 -15 +55 -45 = 110
7) (35 +75) + (345 -35 -75) = 35 +75 +345 -35 -75 = 345
8) (2002 -79 +15) - (-79 +15 )= 2002 -79 +15 +79 -15 = 2002
9) -(515 -80 +91) - (2003+80-91) =-515+80-91-2003-80+91=-2518
10) 25-(-17) +24 -12 = 25 +17 +24 -12 = 54
11) 235 - (34 +135) -100 = 235 - 34 -135 -100 = -34
12) (13 +49 ) - (13 -135 +49) = 13 +49 -13 +135 -49 =135
13) (18 +29) + (158 -18 -29) = 18 +29 +158 -18 -29 = 158
Bài 3:
1) (-37)+14+26+37 = (14+26)+37-37 = 40
2) (-24) +10+6+24 = (10 +6) +24 -24 = 16
3) 15 +23 + (-25 )+(-23) = (15-25)+(23-23) = -10
4) 60+33+(-50) + (-33) = (60-50)+(33-33) = 10
5) (-16)+(-209)+(-14) +209 = (-16-14)+(209-209) = -30
6) (-12)+(-13)+36+(-11) = (-12-13-11)+36 = (-36)+36 = 0
7) -16 +24 +16 -34 = (-16 +16)+(24-34) = -10
8) 25 +37-48-25-37 = (25-25)+(37-37)-48 = -48
9) 2575+37-2576-29 = (2575-2576)+(37-29)= -1+8 = 7
10) 34+35+36+37-14-15-16-17= (34-14)+(35-15)+(36-16)+(37-17)
= 20+20+20+20 = 80
11) 4573+46-4573+35-16-5= (4573-4573)+(46-16)+(35-5)
= 30 +30 = 60
12) 32+34+36+38-10-12-14-16-18
= (32-12)+(34-14)+(36-16)+(38-18)-10
= 20+20+20+20-10 = 70
a. = 12 - 25 + 36 - 12 + 36 - 57
= (12 - 12) + (36 + 36) - (25 + 57)
= 0 + 72 - 82
= -10
b. = -23 - 5 + 6 - 17 + 23 - 5 - 83 - 6
= (-23 + 23) + (-5 - 5) + (6 - 6) - (17 + 83)
= 0 + (-10) + 0 - 100
= -110
c.?